SISTEM PENYIMPANAN BAHAN MAKANAN SEMENTARA (PARSTOCK) DI PASTRY SECTION HOTEL PANGERAN PEKANBARU - Dewi Yuli Astri; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the temporary food storage system (parstock) in the pastry section of Pangeran Hotel Pekanbaru. In order for the storage system to run properly, it must carry out several procedures that are a requirement for temporary food storage. Food ingredients are divided into 2 namely Goceries and Perishable materials, the storage of the two materials must be applied in a sustainable manner starting from the type of storage room and equipment, storage arrangement, storage location, storage security and labeling of food ingredients until the ingredients are ready to be processed in order to obtain quality good material. This study used qualitative research methods and to obtain data the authors used interview, observation and documentation techniques. From the result of the research that the author did for 1 month at the Pangeran Hotel Pekanbaru, it was found that the storage system was in good condition but did not meet the correct storage procedures. Keywords : Storage System, Foodstuffs, Groceries, Perishable